Diversity and abundance of bees in Passiflora edulis Sims (Passifloraceae) orchard, associated with Solanum lycocarpum St. Hill. (Solanaceae) - Fernandes, Marcos Gino; Costa, Eduardo Neves [UNESP]; Trindade, Rose Benedita Rodrigues (Universidade Estadual de Maringa, 2025)
Brazil is the third-largest producer of fruits in the world, with yellow passion fruit (Passiflora edulis) as one of its main crops. This species requires cross-pollination, with Xylocopa bees being the primary pollinators due to its self-incompatibility. The presence of Solanum lycocarpum close to passion fruit orchards can serve, due their flowers, as an attraction for pollinating bees, improving the production of the crop. Thus, the objectives of this study were to: i) investigate whether the planting of S. lycocarpum close to the passion fruit orchard increased the richness and abundance of bees; ii) evaluate whether the implementation of trap nests in the passion fruit orchard and close to S. lycocarpum attracted bees to nests in this location; iii) record the time of greatest foraging activity of Xylocopa frontalis in the passion fruit orchard; and iv) quantify the number of natural nests of X. frontalis in the passion fruit orchard during the experimental period. A total of 48 seedlings of S. lycocarpum were planted and divided into two rows along the eastern border of the yellow passion fruit crop. Bees were recorded for 15 minutes each hour from 8:30 am to 3:30 pm. During the remaining 45 minutes, the posts were inspected for natural bee nests. The frequency, abundance, species richness, and indices of Shannon-Winner, Simpson, and Pielou equitability indices were assessed. The most common species were X. frontalis, Apis mellifera, and Trigona spinipes. The flowering of S. lycocarpum near passion fruit orchards positively influenced the increase in the number of nests and species richness of pollinating bees, indicating that this plant, close to passion fruit orchards, can contribute to fruit production. Finally, we showed the preferred times for bee foraging and the period in which insecticide application should be avoided.
Keywords: fruit growing; pollination; trap nests; yellow passion fruit